ChemInform Abstract: Prediction and Synthesis of Strain Tolerant RbCuTe Crystals Based on Rotation of One‐Dimensional Nano Ribbons within a Three‐Dimensional Inorganic Network. Issue 52 (10th December 2015) - Vermeer, Michael J. DeVries; Zhang, Xiuwen; Trimarchi, Giancarlo; Donakowski, Martin D.; Chupas, Peter J.; Poeppelmeier, Kenneth R.; Zunger, Alex
Abstract: Crystals of RbCuTe are synthesized by vacuum annealing of the elements (sealed silica tube, 650 °C, 12 h).